Alelopatia de manjericão e uso do preparado homeopático Nux vomica em alface - Queiroz, Roberto Luiz [UNESP] (2015)
The allelopathy is characterized as an biochemistry activity, capable of influencing negatively the productivity of other plants relatively close, by the activity of the products of the secondary metabolism. Among the plants, it can be pointed the medicinal ones by its quantity and diversity of the category of its compounds as phenols, eugenols, limoneuns, terpenoids, alkaloids, among others, adding up to more the a hundred compound already known in plants. In this context, it can be pointed out the basil as an important commercial plant with its medicinal biochemical compounds for the pharmacological industry, being widely grown in gardens. With the public politics advance by de Decret N. 5.813, from June, 22nd, 2006 (Política Nacional de Plantas Medicinais e Fitoterápicos) and, more recently, with the elaboration of the Relação Nacional de Plantas Medicinais de Interesse ao SUS - RENISUS, containing 71 species, are expressed the objectives to the promotion of the public health and the production of medicinal plants, pointing out the interest of the rural growers in such plants in commercial scale, being, as such, an interesting option for commuting with other conventional species of greens. In such culture, o ecologic grower utilizes of one's empirical knowledge, traditional and scientific of its ecological handling controlling the plague and other diseases taking advantages of the bioactive compounds from several medicinal plants. However, the traditional knowledge is less explored in alelophaty. So, this phenomena can be misjudge as the lack of nutrition of the plant resulting in over feeding the plants with manure without the expected response in vegetal productivity. For propitiating morphological and physiological alterations of the plants, acting in the homeostasis and in the responses of the adverse conditions to the vegetal systems, the aim of this research to evaluate the ...